Aesthetic outcomes of upper eyelid blepharoplasty: a systematic review. Issue 6 (June 2020) - Hollander, M.H.J.; Schortinghuis, J.; Vissink, A.; Jansma, J.; Schepers, R.H.
Abstract: Although upper blepharoplasty is a common cosmetic surgical intervention, a better scientific understanding of the aesthetic results and the preferred surgical technique to achieve the best aesthetic results is still needed. A systematic search using four search engines (PubMed, Embase, CINAHL, and Cochrane) was performed to identify any study on the aesthetic outcome of a solitary upper blepharoplasty; these were subjected to quality assessment for possible inclusion. Eligible studies were randomized controlled trials, controlled trials, cohort studies, and case series ( n ≥ 10). A total of 4043 studies were assessed, of which 26 were included. Aesthetic outcomes included patient-reported outcome measures, scarring, eyebrow height, tarsal platform show, and panel or expert evaluation. Meta-analysis was not possible. Patients were generally satisfied with the aesthetic result and scar formation after an upper blepharoplasty. The amount of tarsal platform show increases, which positively affects the aesthetics. The eyebrow seems to move down slightly. The surgical technique used (skin only or skin/muscle removal) did not influence patient satisfaction or the physician-assessed aesthetic outcomes. Patients are generally satisfied after an upper blepharoplasty. The optimal design of the skin excision is still a matter of debate, especially when addressing lateral hooding. Further objective research is advised.